The Role of Fintech Technology in This Era - Amalia Ramadhani, Mesra; Agussalim (ENCRYPTION: Journal of Information And Technology, 2023)
The development of the industrial world is moving very fast where we can feel one of the changes in the lifestyle of people who use a lot of information technology such as doing the online economy. known as Financial Technology (fintech). Of course, with these developments, of course, there is a threat to the security of personal data. This study aims to determine the use of Fintech Technology (Fintech) in the current era. The purpose of this research is to provide an overview of the development of Financial Technology in the current era, even though there are many obstacles. This research method uses qualitative methods. The results of this study illustrate the growing development of financial technology, so that personal data protection is a form of privacy rights which are individual rights and must be guaranteed by the state.